Balancing the Aggregation of Cobalt Phthalocyanine on Carbon Nanohorn for Efficient H2O2 electrosynthesis in Neutral Electrolyte - Yiqi Ding; Zhuo Xing; Chunguang Kuai; Feng Ryan Wang; Yuzheng Guo (ChemElectroChem)
Abstract Oxygen reduction reaction (ORR) driven by renewable electricity in neutral electrolyte presents a promising way for generating H2O2, which is suitable for daily sanitation and hygiene management. Cobalt phthalocyanine (CoPc) serves as an effective molecular electrocatalyst, providing active sites to facilitate H2O2 generation during ORR through a uniform distribution on carbon supports. However, the catalytic performance currently falls short of industrial application requirements. Herein, we employed carbon nanohorns with abundant oxygen functional groups (CNH(O)) to support CoPc, thereby optimizing the distribution of CoPc and enhancing the generation of active sites with electron‐deficient Co centres. Control experiments and characterizations demonstrate the electron‐deficient of Co centres is dependent on the degree of CoPc aggregation, highlighting a trade‐off between loading weight and distribution of CoPc. Then, a 4% loading weight of CoPc on CNH(O) exhibited the optimal performance of H2O2 generation, achieving a H2O2 current density of 483 mA cm−2 at a potential of 0.3 V vs RHE with a Faradaic efficiency of 64 %.